Changes in Primary School Children's Behaviour, Knowledge, Attitudes, and Environments Related to Nutrition and Physical Activity. (19th March 2013) - Magarey, Anthea Margaret; Pettman, Tahna Lee; Wilson, Annabelle; Mastersson, Nadia
Abstract : Rigorous evaluation of large-scale community-based obesity interventions can provide important guidance to policy and decision makers. The eat well be active ( ewba ) Community Programs, a five-year multilevel, multistrategy community-based obesity intervention targeting children in a range of settings, was delivered in two communities. A comprehensive mixed-methods evaluation using a quasiexperimental design with nonmatched comparison communities was undertaken. This paper describes the changes in primary school children's attitudes, behaviours, knowledge, and environments associated with healthy eating and physical activity, based on data from six questionnaires completed pre- and postintervention by students, parents, and school representatives. As self-reported by students in years from five to seven there were few significant improvements over time in healthy eating and physical activity behaviours, attitudes, knowledge, and perceived environments, and there were few changes in the home environment (parent report). Overall there were considerably more improvements in intervention compared with comparison schools affecting all environmental areas, namely, policy, physical, financial, and sociocultural, in addition to improvements in teacher skill and knowledge. These improvements in children's learning environments are important and likely to be sustainable as they reflect a change of school culture. More sensitive evaluation tools may detect behaviour changes.